The Influence of Asset Turnover and Company Characteristics on Economic Profitability in Restaurant, Hotel and Tourism Sub-Sector Companies Listed on The BEI - Ines Fatikasari; Ilham Ramadhan Ersyafdi; Fitriah Ulfah (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2021)
Abstract In the business world, a company must follow economic developments for the sustainability of its business activities. In addition to increasing profits, companies must also increase profitability. One way to assess profitability is economic profitability. Economic profitability is the ability of a company to get the desired profit with the source of capital owned either from foreign capital or own capital. The COVID-19 pandemic that occurred in all countries in the world was able to hit various business fields, such as the restaurant, hotel and tourism sub-sectors. The purpose of this study is to find out what factors can affect the economic profitability of companies in the restaurant, hotel, and tourism sub-sectors listed on the Indonesia Stock Exchange (IDX). The population in this study is the restaurant, hotel and tourism sub-sector companies listed on the Indonesia Stock Exchange for the period 2012-2019. The sample used is 6 companies that have been selected using purposive sampling method. The analysis technique in this study uses multiple linear regression analysis. The result of the research shows that receivables turnover affects economic profitability. Meanwhile, cash turnover, fixed asset turnover, working capital turnover, company growth, and company size do not affect economic profitability. Keywords: Economic Profitability; Asset Turnover; Company Characteristic.